Tea polyphenols extracted from fresh young tea leaves exhibits antibacterial activity against some bacterial species: An in vitro study - Sikder, Md. Belal Hossain; Alam, Shafiul; Moazzem, Md. Shakir; Ali, Hazrat; Al-Mamun, Abdullah; Rashid, Shah Samiur (Chulalongkorn University, Bangkok, 2020)
Background: Natural products are rich sources of therapeutic agents for remedy, prevention and cure of diseases.Currently, many strains of bacteria have become resistant to many of the conventional antibiotics. So, in-depth researches should be focused on the antibacterial activity of natural compounds derived from natural sources. Objectives: The purposes of this study were to determine the antibacterial activity of polyphenols extracted from fresh young tea leaves against Escherichia coli, Pseudomonas spp., Klebsiella spp. and Staphylococcus aureus.